MRI Based Morphometry of Shoulder Joint - Manoj, Megha; Kashikar, Shivali Vaibhav; Dhande, Rajasbala Pradeep (International Journal of Psychosocial Rehabilitation, 2020)
Understanding the morphometric differences of shoulder joint with gender and increasing age would help us better understand the pathology of the various conditions associated with the joint and thereby plan therapy accordingly. Objectives: In this study we aim to evaluate the morphometry of shoulder joint using MRI of patients who present with shoulder pain, the anatomical variations and resulting disability. Methodology: A cross-sectional study will be done at Acharya Vinoba Bhave Rural Hospital, Sawangi, involving 75 patients who present with shoulder pain for MRI. The sample will be selected randomly and glenoid dimensions like glenoid version, height, width, coronal diameter and glenoid labrum, humeral head coronal diameter, coracoid process dimensions like length, width and index, type of acromion, subacromial distance and coracohumeral distance will be evaluated using T1, T2 and PD MRI sequences. These dimensions would be compared gender and age wise and correlated with their resultant disability. Results: After appropriate statistical analysis, we expect to find gender and age wise differences in glenohumeral, coracoid and acromion dimensions, and a positive association of these dimensions with their disabilities. Conclusion: In this observational study, we expect variations in glenoid, humeral, coracoid, acromion, subacromial distance (SAD) and coracohumeral distance (CHD) dimensions with gender and increasing age. We also expect to find a positive association between coracohumeral distance (CHD) and subacromial distance with subscapularis and supraspinatus impingement syndromes respectively.